Eastern law reporter, Canada (Carswell, 1906)
Containing judgments of the courts of Nova Scotia, New Brunswick and Prince Edward Island, together with a selection of cases decided by the Judicial committee of the Privy council, Supreme and Exchequer courts of Canada, in cases arising in such provinces.